2004
DOI: 10.1037/0022-3514.87.3.340
|View full text |Cite
|
Sign up to set email alerts
|

Inside the Mind Reader's Tool Kit: Projection and Stereotyping in Mental State Inference.

Abstract: Mental state inferences-judgments about what others think, want, and feel-are central to social life. Models of "mind reading" have considered main effects, including social projection and stereotyping, but have not specified the conditions that govern when these tools will be used. This article develops such a model, claiming that when perceivers assume an initial general sense of similarity to a target, they engage in greater projection and less stereotyping. Three studies featuring manipulations of similari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
354
0
8

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 371 publications
(377 citation statements)
references
References 51 publications
15
354
0
8
Order By: Relevance
“…These theories suggest that people use their own mental states to infer others' beliefs and behaviors (e.g., Hoch, 1987;Krueger, 1998;Marks & Miller, 1987;Nickerson, 1999;Ross, Greene, & House, 1977). Recently, several researchers have argued that this is true mostly for similar and close others (e.g., Ames 2004aAmes , 2004bMitchell, Banaji, & Macrae, 2005;Schul & Vinokur, 2000). For example, recent work by Ames has shown that higher levels of perceived similarity to a target were associated with greater projection and less stereotyping (Ames, 2004a;2004b).…”
Section: Projectionmentioning
confidence: 99%
See 1 more Smart Citation
“…These theories suggest that people use their own mental states to infer others' beliefs and behaviors (e.g., Hoch, 1987;Krueger, 1998;Marks & Miller, 1987;Nickerson, 1999;Ross, Greene, & House, 1977). Recently, several researchers have argued that this is true mostly for similar and close others (e.g., Ames 2004aAmes , 2004bMitchell, Banaji, & Macrae, 2005;Schul & Vinokur, 2000). For example, recent work by Ames has shown that higher levels of perceived similarity to a target were associated with greater projection and less stereotyping (Ames, 2004a;2004b).…”
Section: Projectionmentioning
confidence: 99%
“…Recently, several researchers have argued that this is true mostly for similar and close others (e.g., Ames 2004aAmes , 2004bMitchell, Banaji, & Macrae, 2005;Schul & Vinokur, 2000). For example, recent work by Ames has shown that higher levels of perceived similarity to a target were associated with greater projection and less stereotyping (Ames, 2004a;2004b). In addition, it has been shown that interpersonal closeness increases the overlap between mental representations of the self and mental representation of socially close others (e.g., Aron et al, 1991;Cialdini, Brown, Lewis, Luce, &Neuberg, 1997;Mashek, Aron, & Boncimino, 2003;Smith, Coats, & Walling, 1999).…”
Section: Projectionmentioning
confidence: 99%
“…We expected that people rely more on the self when predicting a similar other than when predicting a dissimilar other (Ames, 2004). When predicting dissimilar others, no order effect should emerge.…”
Section: Studymentioning
confidence: 99%
“…People should make use of other sources of information instead, such as stereotype knowledge (cf. Ames, 2004). Because self-predictions and predictions of the older person should involve, at least in part, independent processes and strategies for prediction, we expected no order effects on self-other correspondence for the prediction of older persons.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation